Presidential elections - Russia 2012 - Frolova, Ksenia (2012)
The uniqueness of 2012 Presidential election campaign lies in some new trends: for the first time Internet played such an important role in influencing voters. It's not just about traditional official websites of the candidates, but first and foremost about campaigning in blogs and social networks. The opposition, including "off-system" one (which is advocating the overthrow of the ruling elite), was much more active in this field. The Internet space became the scene of this conflict, and we should expect that it would only escalate in the future.